BlendMode
public
final
enum
BlendMode
extends Enum<BlendMode>
java.lang.Object | ||
↳ | java.lang.Enum<android.graphics.BlendMode> | |
↳ | android.graphics.BlendMode |
Summary
Enum values | |
---|---|
BlendMode |
CLEAR
|
BlendMode |
COLOR
|
BlendMode |
COLOR_BURN
|
BlendMode |
COLOR_DODGE
|
BlendMode |
DARKEN
|
BlendMode |
DIFFERENCE
|
BlendMode |
DST
|
BlendMode |
DST_ATOP
|
BlendMode |
DST_IN
|
BlendMode |
DST_OUT
|
BlendMode |
DST_OVER
|
BlendMode |
EXCLUSION
|
BlendMode |
HARD_LIGHT
|
BlendMode |
HUE
|
BlendMode |
LIGHTEN
|
BlendMode |
LUMINOSITY
|
BlendMode |
MODULATE
|
BlendMode |
MULTIPLY
|
BlendMode |
OVERLAY
|
BlendMode |
PLUS
|
BlendMode |
SATURATION
|
BlendMode |
SCREEN
|
BlendMode |
SOFT_LIGHT
|
BlendMode |
SRC
|
BlendMode |
SRC_ATOP
|
BlendMode |
SRC_IN
|
BlendMode |
SRC_OUT
|
BlendMode |
SRC_OVER
|
BlendMode |
XOR
|
Public methods | |
---|---|
static
BlendMode
|
valueOf(String name)
|
static
final
BlendMode[]
|
values()
|
Inherited methods | |||||||||||||||||||||||
---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|---|
| |||||||||||||||||||||||
| |||||||||||||||||||||||
|
Enum values
CLEAR
public static final BlendMode CLEAR
αout=0
Cout=0
COLOR
public static final BlendMode COLOR
COLOR_BURN
public static final BlendMode COLOR_BURN
αout=αsrc+αdst−αsrc∗αdst
Cout={Cdst+Csrc∗(1−αdst)Cdst=αdstαdst∗(1−αsrc)Csrc=0αsrc∗(αdst−min(αdst,(αdst−Cdst)∗αsrc/Csrc))+Csrc∗(1−αdst)+αdst∗(1−αsrc)otherwise
COLOR_DODGE
public static final BlendMode COLOR_DODGE
αout=αsrc+αdst−αsrc∗αdst
Cout={Csrc∗(1−αdst)Cdst=0Csrc+αdst∗(1−αsrc)Csrc=αsrcαsrc∗min(αdst,Cdst∗αsrc/(αsrc−Csrc))+Csrc∗(1−αdst+αdst∗(1−αsrc)otherwise
DARKEN
public static final BlendMode DARKEN
αout=αsrc+αdst−αsrc∗αdst
Cout=(1−αdst)∗Csrc+(1−αsrc)∗Cdst+min(Csrc,Cdst)
DIFFERENCE
public static final BlendMode DIFFERENCE
αout=αsrc+αdst−αsrc∗αdst
Cout=Csrc+Cdst−2∗min(Csrc∗αdst,Cdst∗αsrc)
DST
public static final BlendMode DST
αout=αdst
Cout=Cdst
DST_ATOP
public static final BlendMode DST_ATOP
αout=αsrc
Cout=αsrc∗Cdst+(1−αdst)∗Csrc
DST_IN
public static final BlendMode DST_IN
αout=αsrc∗αdst
Cout=Cdst∗αsrc
DST_OUT
public static final BlendMode DST_OUT
αout=(1−αsrc)∗αdst
Cout=(1−αsrc)∗Cdst
DST_OVER
public static final BlendMode DST_OVER
αout=αdst+(1−αdst)∗αsrc
Cout=Cdst+(1−αdst)∗Csrc
EXCLUSION
public static final BlendMode EXCLUSION
αout=αsrc+αdst−αsrc∗αdst
Cout=Csrc+Cdst−2∗Csrc∗Cdst
HARD_LIGHT
public static final BlendMode HARD_LIGHT
αout=αsrc+αdst−αsrc∗αdst
Cout={2∗Csrc∗CdstCsrc∗(1−αdst)+Cdst∗(1−αsrc)+2∗Csrc≤αsrcαsrc∗αdst−2∗(αdst−Cdst)∗(αsrc−Csrc)otherwise
HUE
public static final BlendMode HUE
LIGHTEN
public static final BlendMode LIGHTEN
αout=αsrc+αdst−αsrc∗αdst
Cout=(1−αdst)∗Csrc+(1−αsrc)∗Cdst+max(Csrc,Cdst)
LUMINOSITY
public static final BlendMode LUMINOSITY
MODULATE
public static final BlendMode MODULATE
αout=αsrc∗αdst
Cout=Csrc∗Cdst
MULTIPLY
public static final BlendMode MULTIPLY
αout=αsrc+αdst−αsrc∗αdst
Cout=Csrc∗(1−αdst)+Cdst∗(1−αsrc)+(Csrc∗Cdst)
OVERLAY
public static final BlendMode OVERLAY
αout=αsrc+αdst−αsrc∗αdst
Cout={2∗Csrc∗Cdst2∗Cdst<αdstαsrc∗αdst−2(αdst−Csrc)(αsrc−Cdst)otherwise
PLUS
public static final BlendMode PLUS
αout=max(0,min(αsrc+αdst,1))
Cout=max(0,min(Csrc+Cdst,1))
SATURATION
public static final BlendMode SATURATION
SCREEN
public static final BlendMode SCREEN
αout=αsrc+αdst−αsrc∗αdst
Cout=Csrc+Cdst−Csrc∗Cdst
SOFT_LIGHT
public static final BlendMode SOFT_LIGHT
Where m={Cdst/αdstαdst>00otherwise
g={(16∗m∗m+4∗m)∗(m−1)+7∗m4∗Cdst≤αdst√m−motherwise
f={Cdst∗(αsrc+(2∗Csrc−αsrc)∗(1−m))2∗Csrc≤αsrcCdst∗αsrc+αdst∗(2∗Csrc−αsrc)∗gotherwise
αout=αsrc+αdst−αsrc∗αdst
SRC
public static final BlendMode SRC
αout=αsrc
Cout=Csrc
SRC_ATOP
public static final BlendMode SRC_ATOP
αout=αdst
Cout=αdst∗Csrc+(1−αsrc)∗Cdst
SRC_IN
public static final BlendMode SRC_IN
αout=αsrc∗αdst
Cout=Csrc∗αdst
SRC_OUT
public static final BlendMode SRC_OUT
αout=(1−αdst)∗αsrc
Cout=(1−αdst)∗Csrc
SRC_OVER
public static final BlendMode SRC_OVER
αout=αsrc+(1−αsrc)∗αdst
Cout=Csrc+(1−αsrc)∗Cdst
XOR
public static final BlendMode XOR
αout=(1−αdst)∗αsrc+(1−αsrc)∗αdst
Cout=(1−αdst)∗Csrc+(1−αsrc)∗Cdst